DAMPAK ARUS KAS OPERASI, LABA AKUNTANSI, DAN UKURAN PERUSAHAAN TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2020-2022 - Natrion; Dеոոy AIfiaոsyah (Jurnal Liabilitas, 2023)
Investment is the act of investing money or capital in one or more types of assets for a limited period for the purpose of achieving income or increasing value, which is commonly referred to as Stock Return. Stock Return is the return effect of investment. This study aims to determine the effect of operating cash flow, accounting profit, and company size on stock returns. The research design uses causal research. The population and sample for this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020 – 2022. The data collection technique in this study used a purposive sampling technique. The data used is secondary data obtained from the Indonesian Stock Exchange (IDX) and data analysis using Multiple Linear Regression analysis. The results of the study prove that accounting profit has no significant effect on stock returns, while operating cash flow and company size have no significant effect on stock returns. The magnitude of the influence of the independent variable on the dependent variable is 12.4%.